Optical Property and Photoelectrical Performance of a Low-bandgap Conducting Polymer Incorporated with Quantum Dots Used for Organic Solar Cells - Thao, Tran Thi; Hai, Vu Thi; Dinh, Nguyen Nang; Trong, Le Dinh (Communications in Physics, 2015)
By using spin-coating technique, a low bandgap conjugated polymer, poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopen-ta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (PCPDTBT)  and its composite thin films have been prepared. The optical absorption and photoconductive properties with over a wide spectral range, from 350 to 950  nm, were characterized. The obtained results showed that PCPDTBT:10 wt% CdSe  composite is the most suitable for efficient light-harvesting in polymer-based photovoltaic cells. The photoelectrical conversion efficiency (PCE) of the device with  a multilayer structure of ITO/PEDOT/ PCPDTBT:CdSe /LiF/Al  reached a value as large as 1.34% with an open-circuit voltage (Voc) = 0.57 V, a short-circuit current density (Jsc) = 4.29 mA/cm2, and a fill factor (FF) = 0.27. This suggests a useful application in further fabrication of quantum dots/polymers based solar cells.